Superior oxidation and spallation resistant NiCoCrAlY bond coat via homogenizing the yttrium distribution. (October 2019) - Lu, Jie; Chen, Ying; Zhang, Han; Zhao, Chunshan; Zhao, Xiaofeng; Guo, Fangwei; Xiao, Ping
Graphical abstract: Highlights: The yttrium in the form of fine Ni-Y enriched precipitates and nano-sized Y2 O3 particles. The optimization of yttrium distribution in the bond coat can significantly enhance the spallation resistance of TGO. Sulfur segregation to interface is well inhibited due to the uniform distribution of yttrium. Interfacial imperfections (interfacial pores and oxide intrusions) are well suppressed due to the uniform distribution of yttrium. Abstract: We present a novel approach to significantly improve the oxidation and spallation resistance of a NiCoCrAlY bond coat by homogenizing the yttrium distribution via powder milling and subsequent spark plasma sintering. The NiCoCrAlY bond coat fabricated by this method exhibits a much lower oxidation rate and a significantly better spallation resistance after isothermal oxidation at 1150 °C, compared with the counterpart fabricated from the un-milled powder. To understand the improvement in oxidation resistance, the microstructure of the bond coats, the chemistry and microstructure of the thermally grown oxides (TGOs), the TGO stresses and the interfacial chemistry are systemically investigated.